Ad libitum suckling by a foster calf in the presence or absence of the cow's own calf prolongs postpartum anestrus to first ovarian cycle - Lamb, G.C.; Smith, J.M.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Five treatments were initiated approximately 15 days after calving: 1) calf was weaned from its dam (CW); 2) calf was present continually with its own dam (CP-O); 3) calf was present continually with its own dam but contact with the udder was restricted (CR); 4) foster calf was pre sent continually but the cow's own calf was absent (CP-F); and 5) foster calf was present continually, and the dam's own calf was present but restricted (CR+F). Cows weaned at 15 days (CW) cycled in about 2 weeks, whereas cows in the CR treatment cycled 1 week later, and cows in the CP-O treatment did not cycle for about 5 weeks. Cows fostering calves in the presence (CR+F) or absence (CP-F) of their own calves had extended anestrus periods similar to those in cows nursing their own calve s (CP-O). If a cow bonds with a foster calf (as in the CP-F treatment), then the duration of anestrus is lengthened. We conclude that anestrus is prolonged only when milk is removed by a calf (her own or a foster calf) to which the cow is bonded.
Keywords: Beef; Suckling; Anestrus; Cow; Postpartum